Establishing national stakeholder priorities for quality improvement in pediatric trauma care: Consensus results using a modified Delphi process. Issue 4 (17th October 2022) - Melhado, Caroline G.; Yorkgitis, Brian K.; Patel, Bhavin; Remick, Katherine; Macias, Charles G.; Dingeldein, Michael W.; Gray, Lisa; Jensen, Aaron R.
Abstract : This is a modified Delphi process study recruiting key pediatric trauma stakeholders to determine four consensus national priorities for improving system-level quality and outcomes across the continuum of pediatric trauma care. Abstract : BACKGROUND: Quality improvement efforts within pediatric trauma centers (PTCs) are robust, but the majority of children do not receive initial postinjury care at PTCs. Disparities in access to quality trauma care remain, particularly for children who initially access the trauma system outside of a PTC. The purpose of this project was to identify unmet needs for injured children within the pediatric emergency care system and to determine national priorities for quality improvement across the continuum of pediatric trauma care. METHODS: A panel of delegates representing patients and families, prehospital providers, federal funding partners, nurses, and physicians was recruited from 10 national stakeholder organizations. Potential targets were identified using an initial stakeholder meeting followed by a free text response survey. Free text items were coded and condensed as themes and then ranked by the panel using a modified Delphi approach to determine consensus priorities. Items not achieving >35% prioritization on a given iteration were dropped from subsequent iterations. Consensus was defined as 75% of members designating an item as a top-four priority. RESULTS: Nineteen themes were identified as potential targets for QI initiatives. Four iterations of panel ranking were used to achieve consensus, with four priorities identified: (1) creation of a toolkit and standard provider training for pediatric trauma triage, shock recognition, and early recognition for need to transfer to higher level of care; (2) development of minimum standards for pediatric trauma resuscitation and stabilization capability in nonpediatric centers; (3) facilitating creation of local nursing and physician champions for pediatric trauma; and (4) development and dissemination of best-practice guidelines to improve imaging practices for injured children. CONCLUSION: System-level quality improvement priorities for pediatric trauma care should focus resources on developing and implementing minimum pediatric standards for injury care, frontline provider training, stabilization protocols, imaging guidelines, and local pediatric champions. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :